SLOW MEDICINE: A PHILOSOPHICAL CONCEPTION FOR A HUMANIZED GERIATRIC PRACTICE - Patrick Alexander Wachholz; José Carlos Aquino de Campos Velho (Brazilian Society of Geriatrics and Gerontology, 2021)
Expansion of the concept of health, care fragmentation, and technology overvaluation have fostered discussions about the limitations of the biomedical model. The post-COVID-19 era can be one of the largest and best windows of opportunity for implementation of interventions aimed at promoting health equity, particularly in geriatrics. The mission of Slow Medicine can be summarized in three keywords: measured, because it acts with moderation, gradually and without waste; respectful, because it seeks to preserve the dignity and values of each person; and equitable, because it is committed to ensuring access to appropriate care for all. Operationally, the Slow Medicine movement is known internationally for the "Doing more does not mean doing better" campaign, whose objective is essentially to reflect upon and try to engage physicians in reflective practices to avoid the overuse of medical resources, both diagnostically and therapeutically. In this article, we present a brief historical summary and the principles that guide the praxis of the Slow Medicine movement, and invite the reader to reflect on a "geriatrics without haste."